2011
DOI: 10.5012/jkcs.2011.55.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectroscopic Characterization of Manganese(II), Iron(III) and Cobalt(III) Complexes of Macrocyclic Ligand. Potential of Cobalt(III) Complex in Biological Activity

Abstract: ABSTRACT. A new series of manganese(II), iron(III) and cobalt(III) complexes of 14-membered macrocyclic ligand, (3,6, 10,13,16,19-hexaazabicyclo[6.6.6]icosane-1,8-diamine) have been prepared and characterized by elemental analyses, IR, UV-VIS, 1 H-and 13 C-NMR spectra, magnetic susceptibilities, conductivities, and ESR measurements. Molar conductance measurements in DMF solution indicate that the complexes are electrolytes. The ESR spectrum for cobalt(III) complex in CD3OD+10%D2O after exposure to 60 Co-γ-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…The antibacterial and antifungal screening with the hydrazine carbothioamide were investigated. The found that the ligand was biologically inactive against gram positive bacterium (Bacillus subtills and gram-negative bacterium (E. coli) [15]. )ylidene acetate in good to excellent yield.…”
Section: Introductionmentioning
confidence: 97%
“…The antibacterial and antifungal screening with the hydrazine carbothioamide were investigated. The found that the ligand was biologically inactive against gram positive bacterium (Bacillus subtills and gram-negative bacterium (E. coli) [15]. )ylidene acetate in good to excellent yield.…”
Section: Introductionmentioning
confidence: 97%